2005
DOI: 10.1590/s0043-31442005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial isolates from patients in an intensive care unit, and associated risk factors

Abstract: A retrospective one-year analysis of blood, sputum and urine samples taken from all patients admitted for more than 48 hours to the Intensive Care Unit at the University Hospital of the West Indies (UHWI) was undertaken. Positive trapped sputum cultures were found in 50% of patients, positive blood cultures in 32.7% and positive urine cultures in 23.1%. Gram-negative organisms predominated especially Pseudomonas aeruginosa (41.3%) and Acinetobacter spp (33.5%). Coagulase-negative staphylococcus (20%) and strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
5
14
1
1
Order By: Relevance
“…Each invasive procedure performed poses a risk of infection. There was a direct correlation between central venous catheterization, tracheostomy, mechanical ventilation and the risk of infection in our study, in agreement with the results of other studies [7,11,14,18]. …”
Section: Discussionsupporting
confidence: 93%
“…Each invasive procedure performed poses a risk of infection. There was a direct correlation between central venous catheterization, tracheostomy, mechanical ventilation and the risk of infection in our study, in agreement with the results of other studies [7,11,14,18]. …”
Section: Discussionsupporting
confidence: 93%
“…Multivariate analysis showed a 3.57 times higher risk of infection in newborns previously exposed to antimicrobial agents. Similar results have been reported by other investigators 2,32. Lopes et al33 found an association between previous antibiotic treatment and a higher mortality rate in premature low-weight newborns.…”
Section: Discussionsupporting
confidence: 90%
“…13 Earlier similar findings have been reported. 14 , 15 However, unlike the present study, it has shown that the independent risk factors for late versus early VAP acquired in ICU was advanced age. 16 …”
Section: Discussioncontrasting
confidence: 88%